THEO VAN LEUWEN'S THEORY OF INCLUSION IN CRIMINAL NEWS ON FACEBOOK: A CRITICAL DISCOURSE ANALYSIS - Suharni, Suharni; Saidi, Siti Bahirah; Medina, Samantha (Journal of Pragmatics and Discourse Research, 2022)
Recently, there has been an increase in crime, with one of the contributing factors being the increase in the need for life and other conflicts of interest. The crimes were eventually made public by some media outlets, one of which was the social media site Facebook, among others. This research aims to attempt to uncover how the criminal's discourse can be expressed succinctly through the use of critical discourse analysis from Theo Van Leeuwen's point of view by employing critical discourse analysis. This research operates qualitative research models in conjunction with content analysis techniques. According to the findings of this study, there are several concepts of sentences, including (1) determination-indetermination, (2) assimilation-individualization, (3) nomination-identification, (4) dissociation, and (5) categorization, among others. Based on the research findings, it can be concluded that when releasing criminal news, the author (journalist) still appears partial to the executor or actor by encircling the criminal perpetrators or perpetrators. Some have explained that, despite the perpetrator's already known, the news writer did not write the story.